AR AND HE ISOTOPES IN THE DOVYREN MAFIC-ULTRAMAFIC INTRUSION - Konnikov E.G.; Prasolov E.M.; Tokarev I.V.; Kislov E.V.; Orsoev D.A. (My University, 2002)
The paper presents results of Ar and He isotopic studies in rocks and sulfide ores of the Late Precambrian Dovyren dunite-troctolite layered intrusion (Northern Baikal region). The 3He/4He and 40Ar/36Ar ratios in the intrusion are similar to those in other mafic intrusions in the continental crust, and the gases in fluid inclusions bear a significant crustal component. The lowest 3He/4He and 40Ar/36Ar ratios in sulfide ores hosted by the intrusion, about those in crustal fluids, indicate involvement of the latter in magmatic mineralization.